Achyrocline satureioides essential oil-loaded in nanocapsules reduces cytotoxic damage in liver of rats infected by Trypanosoma evansi - Ritter C.S. (2017)
© 2016 Elsevier LtdThe aim of this study was to evaluate whether the treatment with Achyrocline satureioides essential oil-loaded in nanocapsules (AS-NC) is able to protect the hepatic tissue against cytotoxic damage caused by Trypanosoma evansi. Thus, the rats were divided into four groups (n = 6 per group): uninfected/saline, uninfected/AS-NC, infected/saline, and infected/AS-NC. At day 4 post-infection (PI), the animals were euthanized and liver and sera samples were collected to perform the hepatic cell viability assay, and to determine seric levels of reactive oxygen species (ROS) and nitric oxide metabolites (NOx). Cell viability decreased (p < 0.05) in the infected/saline group compared to uninfected/saline group, while the treatment with AS-NC avoided this alteration in infected rats. Seric ROS and NOx levels increased (p < 0.05) in the infected/saline group compared to uninfected/saline group, while the treatment with AS-NC avoided this effect on ROS levels of infected rats. In summary, the treatment with AS-NC was able to protect the liver tissue against the cytotoxic effect caused by the parasite by avoiding exacerbated production of ROS.